(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Manual paddy threshing using metal drums with attendant low output and high losses is still being widely used in the Kano-Kura rice cluster. An existing stationary Hold-on thresher designed to address these, was modified and evaluated. The thresher was designed taking all peculiar technical considerations. It was then fabricated using available materials. Paddy Faro 44 variety at a mean moisture content of 13 % (w. b.) was used for evaluation in this study. The independent variables consist of three different speeds 500, 600 and 700 rpm and two feed rates of 200 and 300 kg/h were used. Factorial experiments were conducted in a completely randomized design with three replications. The performance dependent indices used were output capacity, threshing efficiency and cleaning efficiency. The analysis was done using GENSTAT statistical package. It was found out that the effects of variables on the performance indices were highly significant. The mean highest value of the output capacity was 229.09 kg/h at the combination of 700 rpm speed and 300 kg/h feed rate. The mean value obtained for the threshing was 99.99 % and is statistically similar for all the combinations. The cleaning efficiency indicate highest value of 85 % at the combination of 500 rpm speed and 200 kg/h feed rate. T-test for comparison between machine performance and manual threshing showed that the mean value for output capacity, threshing efficiency and cleaning efficiency for the machine are significantly higher than the manual threshing, the, the machine performance has promising prospect.